Retorika Dakwah tentang Muhasabah oleh Ustadzah Halimah Alaydrus Di Youtube - Rany Dahlia Firnandah; Yuangga Kurnia Yahya (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2026)
The phenomenon of digital da'wah has changed the landscape of religious communication, thus allowing preachers to reach a wide audience by utilizing social media platforms such as YouTube, Instagram and TikTok, this phenomenon plays a role against the hegemony of negative content and as an obligation of a Muslim to invite people to goodness, but this is also a challenge for preachers in conveying digital da'wah to rhetorically persuasively so that the message is conveyed spiritual ability to touch mad'u online or offline. In this context, Ustadzah Halimah Alaydrus has a significant influence on the mad'u (audience) even though she does not show her face in her videos and as an effort to deal with various negative content on social media. In this study, the researcher uses a qualitative method with content analysis techniques that seek to explain in depth through 2 da'wah videos. The author limits the discussion by using a phenomenological approach to understand and interpret muhasabah in the perspective of Ustadzah Halimah Alaydrus. The results of the study show that his rhetoric is characterized by a persuasive delivery style that contains ethos (credibility and spiritual authority), logos (arguments based on the Qur'an), with the dominance of pathos (gentle and touching approach) to provide high appeal for Muslim women online pilgrims.